Algorithms and Discrete Applied Mathematics 9th International Conference, CALDAM 2023, Gandhinagar, India, February 9-11, 2023, Proceedings - Bagchi, Amitabha; Muthu, Rahul (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book constitutes the proceedings of the 9th International Conference on Algorithms and Discrete Applied Mathematics, CALDAM 2023, which was held in Gandhinagar, India, during February 9-11, 2023. The 32 papers presented in this volume were carefully reviewed and selected from 67 submissions. The papers were organized in topical sections named: algorithms and optimization; computational geometry; game theory; graph coloring; graph connectivity; graph domination; graph matching; graph partition and graph covering.
Stable Approximation Schemes -- A whirlwind tour of intersection graph enumeration -- Graph modification problems with forbidden minors -- Algorithms & Optimization Efficient reductions and algorithms for Subset Product -- Optimal length cutting plane refutations of integer programs -- Fault-Tolerant Dispersion Resource management in device-to-device communications -- Computational Geometry Algorithms for k-Dispersion for Points in Convex Position in the Plane -- Arbitrary oriented color spanning region for line segments -- Games with a Simple Rectilinear Obstacle in Plane -- Diverse Fair Allocations: Complexity and Algorithms -- Graph Coloring New bounds and constructions for neighbor-locating colorings of graphs -- D K 5-list coloring toroidal 6-regular triangulations in linear time -- On Locally Identifying Coloring of Graphs -- On Structural Parameterizations of Star Coloring -- Reddy Perfectness of G-generalized join of graphs -- Coloring of a superclass of 2K2-free graphs -- The Weak (2,2)-Labelling Problem for graphs with forbidden induced structures -- Graph Connectivity Short cycles dictate dichotomy status of the Steiner tree problem on Bisplit graphs -- Some insights on dynamic maintenance of Gomory-Hu tree in cactus graphs and general graphs -- Monitoring edge-geodetic sets in graphs -- Cyclability, Connectivity and Circumference -- Graph Domination On three domination-based identification problems in block graphs -- Graph modification problems with forbidden minors -- Computational Aspects of Double Dominating Sequences in Graph -- Relation between broadcast domination and multipacking numbers on chordal graphs -- Pushing Cops and Robber on Oriented Graphs -- Mind the Gap: Edge Facility Location Problems in Theory and Practice -- Complexity Results on Cosecure Domination in Graphs -- Kusum and Arti Pandey Graph Matching Latin Hexahedra and Related Combinatorial Structures -- Minimum Maximal Acyclic Matching in Proper Interval Graphs -- Graph Partition & Graph Covering Transitivity on subclasses of chordal graphs -- Maximum subgraph problem for 3-regular Knödel graphs and its wirelength -- Covering using Bounded Size Subgraphs -- Axiomatic characterization of the the toll walk function of some graph classes -- Structural Parameterization of Alliance Problems.
Keywords: Computer science -- Mathematics; Algorithms; Image processing -- Digital techniques; Computer vision; Data structures (Computer science).; Information theory; Mathematics of Computing; Design and Analysis of Algorithms; Computer Imaging, Vision, Pattern Recognition and Graphics; Data Structures and Information Theory